Social Network Analysis of the Save the Malayan Tigers Campaign on Instagram - Reza, Mohammad; Januardi, Arif (STKIP Singkawang, 2025)
Instagram has emerged as a vital platform for wildlife conservation campaigns, offering broad reach and visual interactivity. This study aims to map and analyse the interaction patterns, user engagement, and social structure surrounding the @save_the_malayan_tigers Instagram accounts. This study employed a quantitative descriptive approach using Social Network Analysis (SNA) with NodeXL Pro. Data were collected from 500 recent posts and 100 comments per post. The findings revealed a highly centralised network with the main account acting as a dominant hub in a star-shaped network structure. Several secondary nodes from media, conservation communities, and government accounts extended the campaign to segmented audiences. However, engagement patterns remain largely one-directional, with minimal horizontal interaction. These insights provided strategic recommendations to enhance participatory communication, especially for Generation Z audiences, and emphasise the importance of influencer collaboration and interactive digital features. This study reinforced the role of SNA as a powerful tool for evaluating and improving digital conservation strategies in the social media era.